Pengaruh Self Awareness Terhadap Prestasi Belajar Bahasa Arab Santri Pondok Pesantren Modern Muhammadiyah Boarding School Purwokerto Tahun Ajaran 2022/2023 - Nurdiana, Ryan; Abidin, Munirul; Fauzi, Afif (TarbiyahMU, 2023)
This study aims to test whether there is an influence of self-awareness on the achievement of learning Arabic language students of Muhammadiyah boarding school Purwokerto. Sampling using simple random sampling technique. The sample taken was with 30 students. This study used one independent variable, namely self-awareness (X) and one dependent variable, namely learning achievement (Y). The data used in this study were primary data in the form of questionnaires with 30 respondents and secondary data in the form of the last Arabic test scores. This research method uses ex post facto. The data analysis technique used in this study was simple regression analysis. The results of this study are known significance value (Sign.) of 0.03 which means smaller than 0.05. In addition, the coefficient of determination is obtained with a value of 0.280 or 28.0% so that it can be concluded that variable x (self awareness) has an effect of 28.0% on variable Y (Learning Achievement) Keywords : Influence, Self Awareness, Learning Achievement, Arabic